Glass beads as indicators of contact and trade in Southern Africa ca. AD 900 - AD 1250 - Saitowitz, Sharma Jeanette (Department of Archaeology, 2016)
Luxury goods, used in mediaeval long distance trade ca. AD 900-1250, found an important market among the Iron Age peoples of southern Africa. Indirect evidence of this trade can be seen in the form of archaeological collections of glass beads at sites throughout Africa and Southeast Asia. Thousands of beads have been found at Iron Age sites in the eastern Transvaal Lowveld and at inland sites along the Limpopo Valley and in Botswana. Similar looking types of beads, referred to as small seed beads, were also used in the Muslim mercantile networks and maritime trade in the Indian Ocean, and have been found at coeval sites throughout Southeast Asia, particularly at entrepot ports in India, eastern and western Malaysia and Thailand. At the commencement of the Iron Age occupation of southern African sites, glass beads of any kind were very rare. From ca. AD 900-1000, Islamic influences spread southward along the African east coast. This coincided with the marked increase of glass beads found in southern Africa. Their presence is direct evidence of foreign industry, external trade and contact. The beads are widely believed to have originated in India, and to have been distributed through Arab traders in the Indian Ocean. Exports would have included gold, possibly ivory, and other raw materials. Archaeology has much to contribute towards documenting these activities. The identity and location of the bead sources is important to an understanding of early contact and economic and political developments in southern Africa. The trade connection coincided with the beginning of a critical sequence of events in the cultural history of southern Africa, which culminated in the formation of an incipient state at Great Zimbabwe (AD 1250-1450) from precursors at Mapungubwe and related sites. This period corresponds in time with an important episode in Islamic history, when Muslims conquered Egypt and the Fatimids moved their capital eastwards, in AD 969, from Tunisia to al-Qahira (Cairo) next to the well-established cosmopolitan port entrepot of al- Fustat (now old Cairo). Texts, chronicles, glass weights, scribal notes and receipts confirm that it was already a successful industrial centre with a history of glass-making when the Fatimids gained control of Egypt. In this thesis I have addressed two aspects of research to investigate the trade networks associated with internal and foreign contact: (1) the manufacturing origins of the beads, and, (2) who brought them to southern Africa. Glass material from Egypt, Palestine, Syria and Southeast Asia was used for comparison, and as possible source material. Scientific techniques were used to confirm these operations. The beads were described, classified, and sampled selectively for physical and chemical analysis. Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) was used to determine the rare earth elements (REE) composition. The results show that a particular glass, used to make beads in Egypt, is the same as that used to make some of the beads found at sites in the northern and eastern Transvaal. They document the existence of a trade link with the Mediterranean via the Red Sea 1000 years ago. Until now, both the origin of this contact and the extent of indigenous responses were largely unknown. These findings cast a different light on maritime trade along the east coast of Africa from a millennium ago. Bibliography: pages 175-190.